Arowana Fish Ponds Monitoring System Using CDMA-Based Wireless Communication - Goh, Duan Yeong (Universiti Sains Malaysia, 2017)
Arowana fishes demand good water quality for their healthy growth. A reliable water quality management system is very much required in order to maintain the water quality of the fish pond at optimum level. Manually checking the water quality of each pond one by one is very time consuming and inefficient. This project is aimed to develop a wireless monitoring system for Arowana fish ponds water quality. The water temperature and pH values of each pond are measured using sensors. Each pond sensor is connected to the Arduino Nano with RF module acting as base station, while the main monitoring station of the system uses a BeagleBone Black with Sierra wireless module and RF module. After data encoding, the sensors data from all base stations are sent to main monitoring system via pre-assigned frequency channel in each station. The main monitoring station retrieves data from the frequency channel. After decoding, the data will be sent to the cloud via the LTE network. Data analysis will be done in cloud to determine how the water quality of each pond affects the Arowana fish. Result shows that the system functions properly when the distance of data transmission is shorter than 100m and the maximum percentage error of data from water parameter sensor is acceptable